Exploring the Mediating Role of Attitudes in Enhancing Cultural Awareness Through Knowledge Among Students - Apgrianto, Yohanes Yupilustanaji; Pali, Marthen; Handarini, Dany M; Muslihati, Muslihati; Jatiperwira, Stefan Yudana (Universitas Brawijaya, Indonesia, 2024)
A phenomenon exists among high school students who lack understanding of their cultural awareness and that of others, failing to appreciate ethnic and cultural differences. Consequently, these disparities often become subjects of ridicule or amusement due to each group's varied modes of speech, styles, and customs. To address this issue, cultural awareness is essential, making it pertinent to investigate the impact of knowledge on cultural awareness mediated by attitudes. This study employs a quantitative methodology described as explanatory research. The study used Simple Random sample methodology, whereas the analysis utilized Structural Equation Modelling (SEM). The sample size was determined using the Raosoft sample size calculator with a 5% sampling error rate, resulting in a sample size of 213 students. The study's results indicated that information affects attitudes and cultural awareness, with attitudes potentially mediating the relationship between knowledge and cultural awareness. This study's conclusions pertain to Resource-Based Theory, suggesting that student behavior concerning cultural awareness can be influenced by cognitive expertise, namely in the areas of knowledge, comprehension, application, analysis, synthesis, and assessment. An elevated degree of knowledge can enhance students' attitudes, as seen by behaviors reflecting tolerance, empathy, openness, and respect within the framework of multicultural education. The recommendations for Twelfth-grade high schools to enhance their educational effectiveness with an emphasis on character development.